Pemberdayaan Kelompok PKK â€œPutri Ayuâ€, Desa Terung Wetan, Kecamatan Krian, Sidoarjo Melalui Implementasi Pengolahan Abon dan Dendeng Kluwih - Rosida, Rosida; Putra, AYT (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2019)
Terung Wetan is a village whose people had planted breadfruit tree. Until now, breadfruit has not used optimally by people and only been processed as vegetable for meal. Whereas breadfruit can potentially be processed and developed into product which had economical value and long shelf-life , such as shreded meat-like (=abon), jerked meat-like (=dendeng). The aim of this community service were to improve knowledge and skill of the people in breadfruit processing as shreded meat-like and jerked meat-like, which had cheap, hygiene, long shelf-life and preffered by consumer and to intruduce a good packaging and marketing of the product in order to develop breadfruti product and to increase society income. The methods used in this program were socialization and training in making : shreded meat-like and jerked meat-like, packaging technique and marketing strategy.